DOES INCOME SMOOTHING IMPROVE INFORMATIVENESS OF STOCK PRICES? - Shinta Ningtiyas Nazar; Titik Ekowati; Hery Setiyawan (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
The purpose of this research is to get empirical evidence from effect Income smoothing to Informativeness of Stock Prices in Indonesian Stock Exchange (IDX). Population from this research is take from companies that have been listing Index LQ 45 in IDX form 2003 until 2015. Income Smoothing is masured by Jones’s Model which have been modified by Kothari et. all (2005). Informativeness of stock price using Zarowin and Tucker Model (2006) Future Earnings Response Coeficient, and the relations to earnings persistence, which is can been seen from relation from current earnings dan future earnings. The research is using data from year 2003 until 2015 period, and year 2014 used as terminal year. That found income smoothing have a negative effect to informativeness of stock price and also found the managers’ income smoothing action always decreases earnings from 2013 to 2015. Current earnings have related to future earnings.